Qualitative analysis of the vocabulary used in work logs of a preventive programme for elderly oral function and nutrition. (8th May 2019) - Ito, Kayoko; Edahiro, Ayako; Watanabe, Yoshihiko; Ohara, Yuki; Motohashi, Yoshiko; Morishita, Shiho; Motokawa, Keiko; Watanabe, Yutaka; Hirano, Hirohiko; Inoue, Makoto
Abstract: Background: In Japan, day care services for elders include programmes aimed at improving nutrition and oral and motor functions. Few studies have qualitatively assessed these interventions. Objective: To qualitatively search for the characteristic words used in the work logs of a preventive programme on oral function and nutrition for elders by intervention period and intervention type． Methods: We included 83 participants (81.3 ± 8.2 years) from four day care services in Japan and divided them into the following groups randomly: those who received oral function intervention only, nutritional intervention only and those who received combined oral function plus nutritional intervention. The interventions were conducted twice per month for 24 months. Data from handwritten work logs were entered into a computer as text files. Monitoring of frequently appearing words, co‐occurrence analysis and cross‐tabulation by intervention period and intervention types was conducted using text mining analysis. Results: Correspondence analysis revealed that the words used during 1‐6 months and 7‐12 months were similar in participants' subjective content, and those used in objective content in 13‐18 months and 19‐24 months were similar. These results indicate that subjective improvements increased after 13 months, and it was maintained within 24 months. The combined intervention type is ideal for oral and nutrition problems. Conclusion: Because this text mining approach revealed the changes in the words used and could be used to monitor any subjective improvement, this approach may help evaluate the effects of preventive care.